Development of Wendok-Based Instructional Media Using Role Playing to Improve Fifth-Grade Students’ Speaking Skills - Safaah, Sekar Maula; Airlanda, Gamaliel Septian (Papanda Publisher, 2025)
This study aims to develop a learning medium called Wayang Enceng Gondok (Water Hyacinth Puppets) to enhance the speaking skills of fifth-grade elementary school students through storytelling based on the intrinsic elements of narrative texts. The research employs the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) within a Research and Development (R&D) approach. In the analysis phase, it was found that students faced difficulties in expressing ideas orally and showed low participation in speaking activities. The design phase produced a culturally grounded and environmentally friendly media prototype. During development, the prototype underwent validation by content experts, media experts, and learning experts. Validation results indicated that the media met high-quality standards and were deemed feasible for classroom use. Limited trials showed an increase in student engagement and confidence in speaking. These findings suggest that Wayang Enceng Gondok serves as an effective alternative for Indonesian language instruction, particularly in enhancing oral communication skills. The media fosters an enjoyable and contextual learning environment and promotes active student participation. This study recommends the integration of local culture-based media as a creative and adaptive innovation for primary education.